Map of expected earthquakes algorithm and RTL prognostic parameter: Joint application - Sobolev, G.A.; Zavyalov, A.D.; Tyapkin, Yu.S. (My University, 1999)
The estimation of the seismically dangerous zones of Kamchatkaand Greece for the nearest years is given in this report on the basis of joint application of MEE (Map of expected earthquakes) algorithm and of RTL prognostic parameter. MEE algorithm is based on the analysis of such precursors as b-value, densityof seismogenic faults, number of weak earthquakes, released seismic energy and is used for intermediate-term prediction of M > 5.5 earthquakes. Many year's statistics of using MEE algorithm in various seismically active areas show that up to 80% of M > 5.5 earthquakes occur in the zones selected by this algorithm with the P(D1|K) = 70% conditional probability. The square of the selected zones is no more than 30-35% of the analyzed seismically active area. On the other hand the algorithm RTL is based on detecting of seismic quiescence and foreshockactivation and is used for intermediate-term prediction of strong earthquake (M > 7). Joint application of these two algorithms allows making a prediction of strong earthquakes.